The Effect of Compost Combination on Growth and Yield of Three Varieties Shallot Plants (Allium ascalonicum L). - Eviyati Eviyati; Achmad Faqih; Faris Furqoning Firdaus; Fernanda Candra Kurniawan; Niki Rizqy Anjabi; Aji Ahmad Purnomo (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This experiment aims to determine the effect of the combination of compost on the growth and yield of plants of three varieties of shallots (Allium ascalonicum L). The experiment was carried out in Karangwangun Village, Babakan District, Cirebon Regency - West Java. The research period will be carried out from January to May 2023. The location is located at an altitude of 93 meters above sea level (asl), the soil type of Latosol and Regosol association, including rain type C (moderately wet). The experimental method used is using an experimental method with a Randomized Group Design (RAK) combination pattern, the treatment consists of two factors that are repeated three times. The first factor is compost which consists of three levels, namely compost 10 tons / ha, compost 15 tons / ha, and compost 20 tons / ha. While the second factor is varieties consisting of three levels, namely pancasona varieties, violetta varieties, and bima varieties. The main observation data were processed using linear model statistical tests, fingerprint analysis, and scott-knot group follow-up test analysis. To determine the correlation between the treatment and the growth and yield components of shallots, the correlation used is with the Product Moment correlation coefficient. The experimental results showed: (1) The combination of compost treatment and onion plant varieties had an effect on the weight of fresh bulbs per plot and the weight of dry tubers per clump, but did not affect plant height, number of leaves, number of saplings per clump, root volume, number of tubers per plant, diameter of tubers per plant, weight of fresh bulbs per plant, and weight of dry tubers per plot, (2) The highest dry tuber weight per plot was produced by a combination of compost treatment of 10 tons / ha and bima varieties of 3.85 kg / plot or equivalent to 10.26 tons / ha and was not significantly different from other treatment combinations, and (3) There was a significant correlation between plant height and the number of leaves aged 35 HST and 45 HST with seed weights per plot with weak and medium categories. However, there was no apparent correlation between plant height and leaf count aged 25 HST with seed weight per plot with very weak category.